1988
DOI: 10.1088/0029-5515/28/2/002
|View full text |Cite
|
Sign up to set email alerts
|

Neutral particle emission in JET during radiofrequency heating experiments

Abstract: The paper deals with the simulation of neutral particle spectra obtained in JET with an array of four passive neutral particle analysers during discharges with applied stationary or modulated radiofrequency power in the ion cyclotron range of frequencies for a deuterium plasma with hydrogen minority. The distribution function of the hydrogen ions has been computed using a one-dimensional Fokker-Planck equation describing wave-particle interaction by a quasi-linear diffusion term in velocity space. Both station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Radial profiles of charge exchange signals on JET [19] indicate that the power profile is fairly peaked, as theoretically predicted. It may be possible to explain the difference between the JET results and the broad charge exchange profiles observed on PLT by even stronger focusing of the RF power in the larger JET device and better fast ion confinement in JET's higher plasma current and lower ripple.…”
Section: Discussionsupporting
confidence: 78%
“…Radial profiles of charge exchange signals on JET [19] indicate that the power profile is fairly peaked, as theoretically predicted. It may be possible to explain the difference between the JET results and the broad charge exchange profiles observed on PLT by even stronger focusing of the RF power in the larger JET device and better fast ion confinement in JET's higher plasma current and lower ripple.…”
Section: Discussionsupporting
confidence: 78%
“…The case of indirect electron heating raises further questions. This has been discussed in a previous paper [11], where it is shown that during absorption of the ICRF power by minority ions an energetic tail develops, and the high energy part of the tail responds linearly to the modulation if the averaged ICRF power is large compared to the modulation amplitude. Furthermore, for high ICRF power density [12], the dominant Coulomb collisions of minority ions are with electrons.…”
Section: Radius (M)mentioning
confidence: 86%
“…The minority hydrogen tail is monitored by the neutral particle analyser. A set of five analysers scan the plasma cross-section [11]. Only channels viewing the plasma centre exhibit an increase in the neutral flux (Fig.…”
Section: Icrf Modulation In D(h) Plasmas: Correlation With Sawtooth A...mentioning
confidence: 99%
“…To derive n a (r), the neutral transport was modelled by a numerical code, with the condition that the computed energy dependent neutral flux at the plasma edge should fit experimental values (see Ref. [17]).…”
Section: Profile Constraint For the Frascati Tokamakmentioning
confidence: 99%